Out-migration, Wealth Constraints, and the Quality of Local Amenities - Christian Dustmann; Anna Okatenko (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2013)
Using a simple theoretical model, we show that the level of migration costs relative to wealth determines the form of the relation between income and migration intentions, which can be monotonically decreasing, increasing, or inverse U-shaped. Using unique individual level data, covering three geographic regions - sub-Saharan Africa, Asia, and Latin America - we show that migration intentions do indeed respond to individual wealth, and that the patterns differ across the country groups studied in a manner compatible with the predictions of our model. Further, contentment with various dimensions of local amenities plays an important role for migration decisions.
Keywords: O15; R23; J61; 330; Migration and Wealth Constraints; Migration Intentions; Local Amenities